Media Sosial Sebagai Sarana Pembentukan Identitas Politik Pemuda - Alfan Jamil; Fatkurohman Nur Rangga; Rama Dwi Rendra; Thifli Ahmad (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Social media has become a significant element in shaping youth political identity in the digital age. This research aims to explore how symbolic interactions within online spaces influence the construction of political identity among young people. A case study approach was applied, utilizing documentation of academic literature published within the last decade. The analysis employed critical discourse analysis to understand the dynamics of power, symbols, and political representation on social media platforms. The findings reveal that young individuals actively construct their political identity through various digital content forms, such as memes, informative threads, and visual campaigns. Moreover, platform algorithms and online communities play a substantial role in directing political preferences and reinforcing ideological affiliations. The implications highlight the importance of digital literacy and inclusive participation spaces for youth, while also encouraging policy development based on evidence to support the democratization of digital arenas.